Anesthetic Management of Craniotomy for Supratentorial Tumor Resection in a Patient with Femoral-Popliteal Deep Vein Thrombosis: Case Report - Saputra, Tengku Addi; Halimi, Radian Ahmad; Hamzah, Hamzah (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Patients with brain tumors are highly susceptible to venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolism (PE). Approximately 2030% of those with intracranial tumors experience VTE, with factors such as neurological deficits, tissue factor secretion, genetic predispositions, advanced age, and hypertension contributing to the risk. In this case, a 61year woman with Space Occupying Lesion (SOL) Supratentorial at Midfrontal, Hypertension Stage II, Diabetes Mellitus (DM) type 2, and femoral-popliteal DVT undergoes craniotomy in general anesthesia. A thorough preoperative assessment is carried out to increase the success of anesthesia, including Doppler ultrasound assessment, administering anticoagulants up to 24 hours before surgery, and monitoring platelet levels and coagulation profiles. Managing VTE in these patients typically involves anticoagulants, thrombolytics, and thrombectomy tailored to the clinical situation. However, the use of anticoagulants, like heparin, poses a risk of severe bleeding during surgical procedures such as craniotomy. A craniotomy is associated with an increased risk of VTE due to endothelial damage, thromboplastin release, and post-operative immobilization, all contributing to Virchows Triad (venous stasis, endothelial injury, and hypercoagulability). Anesthesiologists must provide meticulous perioperative care, incorporating preoperative and post-operative anticoagulant prophylaxis and being aware of intraoperative bleeding. While VTE is recognized as a common post-operative complication, its impact during surgery and the strategies needed to mitigate related risks are still underexplored. Understanding and addressing these challenges are essential, particularly in patients undergoing craniotomy for intracranial tumors, to improve surgical outcomes and reduce mortality.